Characteristics of Particleboard From Waste Nypa Fruticans Wurmb. (November 2019) - Nurdin, Hendri; Hasanuddin,; Waskito,; Saddikin, M
Abstract: The development of engineering materials has increased its use. Engineering material which is a combination of various materials that can be made into a product, namely particle board. Nypa plants have the potential to be used as engineering materials. Traditionally, the use of nypa fruit has been carried out by the community, but the skin or nypa fiber only becomes waste that is wasted and untapped. The development of a diversified technology process in the utilization of waste into engineering materials in the form of particle boards is very possible. The particle board innovation made from raw nypa fiber as an interior furniture material that has light strength and weight as a substitute for wood. The process of making particle boards with compacting and composition optimization methods is an effort to obtain new material that can be developed and has quality according to JIS A 5908 standard. Efforts to develop new materials with better performance to replace wood products as furniture. Through the improvement of process technology and the potential livelihoods of plant waste in obtaining advanced materials as raw material for innovation in the manufacture of particle board products based on the waste of nypa fruit fiber.